A kind of ultra-light aggregate concrete high-efficiency self-insulating material and preparation method
By optimizing the raw material ratio and preparation method of ultralight aggregate concrete, the existing building exterior insulation materials have been solved, which have short service life, easy to fall off and easily cause fires, and the effects of efficient self-insulating, low density, high strength and low thermal conductivity are achieved.
Patent Information
- Application Number
- CN202411928564.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Existing external insulation materials in building have problems such as short service life, easy to fall off, and easy to cause fires, and cannot improve insulation performance, material density and structural strength at the same time.
Ultralight aggregate concrete is used to efficient self-insulating material, and by optimizing the raw material ratio and preparation method, it includes the use of silicate cement with a specification of 42.5 or above, granulated blast furnace slag powder, aerogel, glass microbeads, fly ash, polystyrene granules, excitants, foaming agents, foam stabilizing agents, water reducing agents and reinforcement agents to form materials with high compressive strength, low thermal conductivity and low density.
It realizes the efficient self-insulating effect of ultra-light aggregate concrete materials, with compressive strength increased by more than 2 times, reduced thermal conductivity by more than 37%, and reduced density by 32%, while meeting the requirements of efficient energy saving and fire-proof performance of buildings.
Smart Images

Figure CN119735403A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal insulation materials, and more specifically, particularly relates to an ultra-light aggregate concrete high-efficiency self-insulating material and a preparation method thereof. Background Art
[0002] Energy conservation is an important part of a resource-saving society. The energy consumption of buildings throughout their life cycle accounts for approximately 51% of the total energy consumption of the whole society. The heat transfer energy consumption of the enclosure system of residential buildings accounts for 42-48% of the building energy consumption. Reducing the energy consumption of the building enclosure system is an important way to achieve building energy conservation, and it is the energy consumption area with the greatest energy-saving potential. Vigorously reducing carbon emissions in construction-related processes will greatly change the concepts and methods of each link of building construction, operation, maintenance and repair, and bring about revolutionary changes in the entire industry.
[0003] However, the existing building exterior insulation technology generally has many disadvantages such as short service life, easy to fall off, and easy to cause fire. It is the mission and responsibility of practitioners in relevant fields of society to accelerate the breakthrough of building energy-saving technology, develop an efficient insulation system for enclosure structures with the same lifespan as the building and A1 fire resistance, and establish a new building energy system as soon as possible.
[0004] Existing exterior wall insulation materials are divided into two categories: organic materials and inorganic materials:
[0005] Relatively mature organic insulation materials mainly include EPS expanded polystyrene board, XPS extruded board, PU polyurethane composite board. Organic insulation materials have the characteristics of low thermal conductivity and good insulation effect, but the fatal disadvantage is poor flame retardancy and fire resistance only reaches B2 or B1 level. They will burn or deform rapidly when exposed to fire or high temperature, becoming the biggest safety hazard of building fires. Commonly used inorganic insulation materials include rock wool insulation board, foamed ceramic board, cement foam board, etc. The fire resistance of these inorganic insulation materials can reach Class A non-combustible, but the compressive strength is very poor, the water absorption rate is high, the insulation effect is poor, and it is difficult to meet the increasingly stringent energy-saving specifications for buildings or public buildings.
[0006] The energy-saving enclosure parts of existing buildings generally adopt external insulation or internal insulation technology.
[0007] External insulation is exposed to the natural environment for a long time and is susceptible to factors such as ultraviolet rays, temperature changes, and rain erosion. It is common to experience cracking, hollowing, and falling off, which affects the insulation effect and building appearance. Insulation materials such as polystyrene boards, extruded boards, and polyurethane all age quickly and are easy to burn, posing fire hazards. Although their fire resistance can be improved by adding flame retardants, they may still burn and release toxic gases under high temperature or open flame conditions. Many building fires are caused by external wall insulation materials. During the construction process, if the base layer is not properly handled, the insulation board is not firmly attached, and the thickness of the finishing mortar is uneven, it is easy to cause large-scale shedding problems in the insulation system, affecting public safety and increasing the difficulty of maintenance. The technical level of construction personnel is required to be high, and the construction quality is difficult to guarantee.
[0008] Internal insulation technology cannot completely eliminate thermal bridges. Thermal bridges are easily formed at the junction of walls and beams, columns, doors and windows, resulting in heat loss and reduced insulation effect. Condensation and mildew may also occur at the thermal bridge site, affecting the quality of the indoor environment. The insulation layer is set on one side of the room, which will occupy a certain amount of indoor space and reduce the usable area. The internal insulation wall will be subject to certain restrictions during decoration. For example, it is not allowed to drill holes or nails at will to avoid damaging the insulation layer. Therefore, improving the insulation performance of wall tiles can ensure a larger effective area indoors while ensuring the indoor insulation performance.
[0009] Categories and advantages and disadvantages of existing building self-insulation materials:
[0010] Autoclaved aerated concrete blocks:
[0011] Advantages: Lightweight, can reduce the weight of buildings. Has certain thermal insulation performance, can effectively reduce energy consumption. Has certain fire resistance, can be produced using industrial waste residue, more environmentally friendly.
[0012] Disadvantages: It cannot independently meet the increasingly stringent requirements of building energy-saving standards. It has low strength and is prone to cracks, which affects the integrity and appearance of the wall. It has strong water absorption, which may cause the wall to become damp and reduce the thermal insulation performance. The construction requirements are relatively high, and anti-crack and moisture-proof treatments are required.
[0013] Ceramic concrete blocks:
[0014] Advantages: It has certain thermal insulation performance. Its strength is higher than that of aerated concrete blocks. It has good durability.
[0015] Disadvantages: It cannot independently meet the increasingly stringent requirements for building energy efficiency standards. It is relatively heavy and increases the burden on the building foundation. The cost is high. The energy consumption in the production process is relatively high.
[0016] Composite insulation blocks:
[0017] Advantages: It integrates multiple insulation materials and has good insulation performance. It can be customized according to different needs.
[0018] Disadvantages: complex structure, uneven internal stress, difficult construction. There are compatibility issues between different materials. High temperature or fire will cause the intermediate insulation material to dissolve, affecting the service life.
[0019] For example, a high-stability ultra-light pumped foam concrete and its preparation method with application number CN202111129272.8 belong to the technical field of building energy-saving materials. The high-stability ultra-light pumped foam concrete includes the following components by mass: 50-60 parts of silicate cement, 5-10 parts of mineral admixtures, 5-10 parts of special fast-hardening cement, 0.5-1 part of inorganic short fibers, 15-25 parts of water, 0.5-1.5 parts of water reducer, 0.1-0.3 parts of graphene oxide aerogel, 4-8 parts of composite foaming agent and 12-18 parts of polystyrene particles. Although this scheme can provide materials with lower density and lower thermal conductivity, the structural strength of the material is still at a low level. In Example 1 of this scheme, the wet density after pumping is 100kg / m3, the thermal conductivity is 0.04W / mK, and the compressive strength is only 0.42Mpa.
[0020] Based on the search of the above patents and combined with the equipment in the prior art, it is found that autoclaved aerated concrete blocks are light and have certain thermal insulation performance, but the strength is low; ceramsite concrete blocks have certain thermal insulation performance and high strength, but are heavy; composite insulation blocks have good thermal insulation performance, but the internal stress is uneven, and high temperature or fire can easily cause the middle insulation material to dissolve. The thermal insulation materials in the prior art cannot guarantee that the three parameters of thermal insulation performance, material density, and structural strength are all at a high level. That is, the industry currently believes that the improvement of these three parameters of the material will conflict with each other.
[0021] Therefore, in view of this, the existing structure and deficiencies are studied and improved, and an ultra-light aggregate concrete high-efficiency self-insulation material and preparation method are provided, in order to achieve a more practical purpose. Summary of the invention
[0022] In order to solve the above technical problems, the present invention provides an ultra-light aggregate concrete high-efficiency self-insulating material and a preparation method, so as to solve the problem that the insulation materials in the prior art cannot ensure that the three parameters of thermal insulation performance, material density and structural strength are all at a high level. That is, the industry currently believes that the improvement of these three parameters of the material will conflict with each other.
[0023] The purpose and effect of the ultra-light aggregate concrete high-efficiency self-insulating material and preparation method of the present invention are achieved by the following specific technical means:
[0024] An ultralight aggregate concrete high-efficiency self-insulating material comprises the following components in parts by weight: 12-60 parts of silicate cement, 4-30 parts of mineral powder, 0.2-1.1 parts of aerogel, 0.2-2.1 parts of glass microspheres, 2-30 parts of fly ash, 1-3 parts of polystyrene particles, 0.2-2.5 parts of activator, 1-6 parts of foaming agent, 0.2-0.5 parts of foam stabilizer, 0.05-0.35 parts of water reducer, 0.5-1.2 parts of reinforcing agent, and 10-40 parts of water.
[0025] Furthermore, the silicate cement is silicate cement with a grade of 42.5 or above as the cementitious material. The silicate cement can be selected from the grades of 42.5, 42.5R, 52.5, and 52.5R.
[0026] Furthermore, the mineral powder is granulated blast furnace slag powder as an auxiliary cementitious material, which optimizes the microstructure of ultra-light aggregate concrete, improves density, reduces cement consumption, improves ultra-light concrete's impermeability, and improves durability against sulfate erosion.
[0027] Furthermore, the aerogel is an inorganic oxide aerogel powder or an organic aerogel powder composed of nano-scale particles, which is used as a thermal insulation material.
[0028] Furthermore, the glass microspheres are hollow glass microspheres used as thermal insulation materials, and can effectively reduce the density of ultra-light aggregate concrete, enhance crack resistance, and increase fluidity.
[0029] Furthermore, the activator is an alkali activator used to activate the potential active components in the mineral powder to change the crystal structure of the mineral powder, thereby improving the early strength and late strength of the ultra-light aggregate concrete.
[0030] Furthermore, the foaming agent is a composite foaming agent.
[0031] Furthermore, the foam stabilizer is triethanolamine or silicone polyether emulsion or silicone polyether emulsion, which can effectively control the structural stability of the bubble liquid film, so that the surfactant molecules are orderly distributed in the bubble liquid film, giving the foam good elasticity and self-repairing ability. The foam stabilizer can be selected from protein foam stabilizers (such as protein hydrolysate), cellulose foam stabilizers (such as HPMC), synthetic surfactant foam stabilizers (such as sodium dodecylbenzene sulfonate), silicone polyether emulsion foam stabilizers, etc.
[0032] Furthermore, the water reducer is a melamine-based high-efficiency water reducer or a polycarboxylic acid-based high-performance water reducer, which reduces water consumption, lowers the water-cement ratio of ultra-light aggregate concrete, improves fluidity, and reduces shrinkage and creep. Water reducers are very necessary in the product production process, and can also improve working performance, reduce water-cement ratio, increase product strength, and save cementitious material consumption. Naphthalene-based water reducers, melamine-based water reducers, aminosulfonate-based water reducers, aliphatic water reducers, and polycarboxylic acid-based water reducers can be selected.
[0033] Furthermore, the reinforcing agent is a nucleating substance.
[0034] Furthermore, the reinforcing agent is nano calcium carbonate, which improves the interface transition zone between ultra-light aggregate and cement paste and improves the integrity and strength of ultra-light aggregate concrete. Other reinforcing agents include: zeolite powder, high-calcium carbonate, lithium slag powder, silica fume, nano alumina, nano titanium dioxide, tricalcium silicate, dicalcium silicate, etc.
[0035] Furthermore, the water is pollution-free natural water.
[0036] Furthermore, the fly ash is fine solid particles in the flue gas ash produced by coal combustion.
[0037] Fly ash, also known as fly ash, is a fine solid particle in the flue gas ash produced by coal combustion, such as the fine ash collected from the flue gas of a thermal power plant. It reacts with cement hydration to produce calcium hydroxide, which reacts secondary to regulate the hydration heat temperature and improve the workability and durability of ultra-light concrete.
[0038] A method for preparing an ultra-light aggregate concrete high-efficiency self-insulating material comprises the following steps:
[0039] S1: Mix silicate cement, mineral powder, fly ash, water reducing agent, activator, reinforcing agent and water in the above proportions and use a mixer to mix into slurry;
[0040] S2: dilute the composite foaming agent with water at a ratio of 1:10, add a foam stabilizer to make the foaming agent foam, and then fully blend it with the slurry;
[0041] S3: Add polystyrene particles, aerogel and glass beads into the slurry and continue stirring.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The present invention overcomes traditional concrete or lightweight aggregate concrete technology by improving concrete raw materials, proportions and preparation methods, and overcomes the technical difficulty of being unable to achieve good performance of the three important indicators of lightweight, high strength and low thermal conductivity self-insulation effect at the same time, breaking the industry's inherent perception for many years that the density, strength and thermal conductivity of ultra-light aggregate concrete high-efficiency self-insulation materials cannot be improved at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The invention discloses a thermal insulation brick made of an ultralight aggregate concrete high-efficiency self-heat-insulating material.
[0045] Figure 2 It is autoclaved aerated concrete brickwork. DETAILED DESCRIPTION
[0046] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0047] In the description of the present invention, unless otherwise specified, "plurality" means two or more than two; the orientations or positional relationships indicated by the terms "upper", "lower", "left", "right", "inner", "outer", "front end", "rear end", "head", "tail", etc. are based on the orientations or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0048] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0049] Embodiment 1:
[0050] Take 19 parts of 52.5 silicate cement, 4 parts of mineral powder, 1.2 parts of polystyrene particles, 3.5 parts of fly ash, 1.1 parts of aerogel, 2.1 parts of hollow glass microspheres, 0.75 parts of activator, 1.5 parts of composite foaming agent, 0.2 parts of foam stabilizer, 0.075 parts of water reducer, 0.75 parts of reinforcing agent, and 13 parts of water to obtain a density of 250kg / m 3 , ultra-light aggregate concrete products with compressive strength not less than 1.5 MPa and thermal conductivity ≤ 0.065W / (m·K).
[0051] Implementation steps:
[0052] 52.5 19 parts of silicate cement, 4 parts of mineral powder, 3.5 parts of fly ash, 0.075 parts of water reducer, 0.75 parts of activator, 0.75 parts of reinforcing agent, add 13 parts of water, and use a mixer to mix into a slurry.
[0053] Dilute 1.5 parts of composite foaming agent with water at a ratio of 1:10, add 0.2 parts of foam stabilizer, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0054] Add 1.2 parts of polystyrene particles, 1.1 parts of aerogel, and 2.1 parts of glass beads to the slurry and stir at 100 rpm for 1-2 minutes.
[0055] Pour into the mold box, cover with plastic film and send to the curing bin for natural curing. The temperature in the curing bin should not be lower than 25 degrees Celsius.
[0056] De-mould after 12 hours.
[0057]
[0058] Embodiment 2:
[0059] Take 45 parts of 42.5 silicate cement, 20 parts of mineral powder, 2.7 parts of polystyrene particles, 25 parts of fly ash, 0.55 parts of aerogel, 1.05 parts of hollow glass microspheres, 1.5 parts of activator, 4 parts of composite foaming agent, 0.3 parts of foam stabilizer, 0.24 parts of water reducer, 0.77 parts of reinforcing agent, and 30 parts of water to obtain a dry density of 425 kg / m 3 , ultra-light aggregate concrete products with compressive strength not less than 5 MPa and thermal conductivity ≤0.12W / (m·K).
[0060] Implementation steps:
[0061] 45 parts of 42.5 cement, 20 parts of mineral powder, 25 parts of fly ash, 0.24 parts of water reducer, 1.5 parts of activator, 0.77 parts of reinforcing agent, and 30 parts of water are mixed into a slurry using a mixer.
[0062] Add 0.9 parts of composite foaming agent to water and 0.3 parts of foam stabilizer in a mixture of 1:10, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0063] Add 2.7 parts of polystyrene particles, 0.55 parts of aerogel, and 1.05 parts of glass beads to the slurry and stir at 100 rpm for 1-2 minutes.
[0064] Pour into the mold box, cover with plastic film and send to the curing bin for natural curing. The temperature in the curing bin should not be lower than 30 degrees Celsius.
[0065] De-mould after 12 hours.
[0066]
[0067] Embodiment three:
[0068] Take 56 parts of silicate cement, 18 parts of mineral powder, 0.8 parts of polystyrene particles, 20 parts of fly ash, 0.6 parts of aerogel, 0.5 parts of hollow glass microspheres, 1.4 parts of activator, 4 parts of composite foaming agent, 0.4 parts of foam stabilizer, 0.2 parts of water reducer, 0.7 parts of reinforcing agent, and 33 parts of water to obtain a density of 725 kg / m 3 , ultra-light aggregate concrete products with compressive strength not less than 10 MPa and thermal conductivity ≤ 0.14W / (m·K).
[0069] Implementation steps:
[0070] 56 parts of Portland cement, 18 parts of mineral powder, 20 parts of fly ash, 0.2 parts of water reducer, 1.4 parts of activator, 0.7 parts of reinforcing agent, and 33 parts of water are mixed into a slurry using a mixer.
[0071] Dilute 4 parts of composite foaming agent with water at a ratio of 1:10, add foam stabilizer, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0072] Add 0.8 parts of polystyrene particles, 0.6 parts of aerogel, and 0.5 parts of glass beads to the slurry and stir at 100 rpm for 1-2 minutes.
[0073] Pour into the mold box or the location where construction is required, cover with plastic film and allow to cure naturally. The ambient temperature should not be lower than 35 degrees Celsius.
[0074] Demould after 6 hours.
[0075]
[0076] Embodiment 4:
[0077] Take 12 parts of 52.5 silicate cement, 4 parts of mineral powder, 1 part of polystyrene particles, 30 parts of fly ash, 1.1 parts of aerogel, 2.1 parts of hollow glass microspheres, 0.5 parts of activator, 1.3 parts of composite foaming agent, 0.2 parts of foam stabilizer, 0.075 parts of water reducer, 0.5 parts of reinforcing agent, and 10 parts of water to obtain a density of 200kg / m 3 , ultra-light aggregate concrete products with compressive strength of 0.8 MPa and thermal conductivity of 0.055W / (m·K).
[0078] Implementation steps:
[0079] 12 parts of Portland cement, 4 parts of mineral powder, 30 parts of fly ash, 0.075 parts of water reducer, 0.5 parts of activator, 0.5 parts of reinforcing agent, and 10 parts of water are mixed into a slurry using a mixer.
[0080] Dilute 1.3 parts of composite foaming agent with water at a ratio of 1:10, add foam stabilizer, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0081] Add 1 part of polystyrene particles, 1.1 parts of aerogel, and 2.1 parts of hollow glass microspheres into the slurry and stir at 100 rpm for 1-2 minutes.
[0082] Pour into the mold box or the location where construction is required, cover with plastic film and allow to cure naturally. The ambient temperature should not be lower than 25 degrees Celsius.
[0083] De-mould after 12 hours.
[0084] Embodiment five:
[0085] Take 60 parts of 52.5 silicate cement, 30 parts of mineral powder, 3 parts of polystyrene particles, 2 parts of fly ash, 0.2 parts of aerogel, 0.2 parts of hollow glass microspheres, 2.5 parts of activator, 1 part of composite foaming agent, 0.5 parts of foam stabilizer, 0.35 parts of water reducer, 1.2 parts of reinforcing agent, and 40 parts of water to obtain a density of 825 kg / m 3 , ultra-light aggregate concrete products with a compressive strength of 13.5 MPa and a thermal conductivity of 0.16 W / (m·K).
[0086] Implementation steps:
[0087] 60 parts of Portland cement, 30 parts of mineral powder, 2 parts of fly ash, 0.35 parts of water reducer, 2.5 parts of activator, 1.2 parts of reinforcing agent, and 40 parts of water are mixed into a slurry using a mixer.
[0088] Dilute 1 part of composite foaming agent with water at a ratio of 1:10, add foam stabilizer, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0089] Add 3 parts of polystyrene particles, 0.2 parts of aerogel, and 0.2 parts of hollow glass microspheres into the slurry and stir at 100 rpm for 1-2 minutes.
[0090] Pour into the mold box or the location where construction is required, cover with plastic film and allow to cure naturally. The ambient temperature should not be lower than 35 degrees Celsius.
[0091] Demould after 6 hours.
[0092] The statistical comparison based on the data of the above five embodiments is as follows:
[0093] Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Embodiment 5 Portland cement 19 45 56 12 60 Mineral powder 4 20 18 4 30 Aerogel 2.1 0.55 0.6 0.2 1.1 Hollow glass microspheres 1.1 1.05 0.5 0.2 2.1 Fly ash 3.5 25 20 2 30 Polystyrene particles 1.2 2.7 0.8 1 3 Stimulant 0.75 1.5 1.4 0.2 2.5 Foaming agent 1.5 4 4 1 6 Foam stabilizer 0.2 0.3 0.4 0.2 0.5 Water reducing agent 0.075 0.24 0.2 0.05 0.35 Enhancer 0.75 0.77 0.7 0.5 1.2 water 13 30 33 10 40 <![CDATA[Density (kg / m 3 )]]> 250 425 725 200 835 Strength(Mpa) ≥1.5 ≥5 ≥10 ≥0.8 ≥13.5 Thermal conductivity W / (m·K) ≤0.065 ≤0.1 ≤0.14 ≤0.055 ≤0.16
[0094] Table 1
[0095] The ultra-light aggregate concrete self-insulating material of the present invention has the following significant advantages and technical effects in specific applications:
[0096] 1. Ultra-light aggregate concrete high-efficiency self-insulating material solves the technical disadvantages of traditional self-insulating materials that they cannot have both low density, high strength and low thermal conductivity. 3The physical properties of different density levels are compared with those of autoclaved concrete (Table 2). Compared with traditional autoclaved aerated concrete materials of the same density level, the compressive strength of ultra-light aggregate concrete high-efficiency self-insulating materials is increased by more than 2 times. Compared with traditional autoclaved aerated concrete materials of the same compressive strength level, the thermal conductivity value of ultra-light aggregate concrete high-efficiency self-insulating materials is reduced by more than 37%: the density weight of ultra-light aggregate concrete compared with traditional self-insulating materials of the same volume and the same compressive strength is reduced by 32%. Ultra-light aggregate concrete has a significantly lower thermal conductivity and smaller density than autoclaved aerated concrete while ensuring a certain compressive strength.
[0097]
[0098] Table 2
[0099] 2. Improve energy efficiency
[0100] 1. Building energy consumption accounts for a large proportion of global energy consumption. Ultra-light aggregate concrete high-efficiency self-insulating materials can significantly reduce the energy demand of buildings during use. By reducing the energy consumption of winter heating and summer cooling, the goal of energy conservation and emission reduction can be achieved. For example, buildings using high-efficiency self-insulating materials can greatly reduce dependence on traditional energy, improve energy efficiency, and contribute to sustainable development.
[0101] 2. Compared with autoclaved concrete, 70% of the raw materials for the production of ultra-light aggregate concrete high-efficiency self-insulating materials are industrial solid waste materials, and no heat energy conversion is required during the production process, which can greatly reduce energy consumption in the production process and effectively reduce carbon emissions.
[0102] 3. Improve building comfort
[0103] 1. Temperature stability
[0104] Ultra-light aggregate concrete self-insulating materials can effectively maintain the stability of indoor temperature. In winter, it prevents the intrusion of cold air from the outside and keeps the room warm; in summer, it blocks the entry of hot air from the outside and reduces indoor temperature fluctuations. This can provide residents and users with a more comfortable indoor environment, reduce the frequent use of air conditioning and heating, and improve the quality of life and work.
[0105] 2. Reduce temperature gradient
[0106] High-efficiency ultra-light aggregate concrete self-insulating materials can reduce the temperature gradient inside the building and avoid uneven hot and cold conditions. This not only improves comfort, but also reduces the risk of structural deformation and damage caused by temperature differences.
[0107] 4. Reduce construction costs
[0108] 1. Long-term energy saving benefits
[0109] Although the initial investment of ultra-light aggregate concrete high-efficiency self-insulating materials may be relatively high, the economic benefits brought by its energy-saving effect in the long run are significant. By reducing energy consumption, the operating costs of the building are reduced. Over time, the energy cost savings can make up for the increase in the initial investment and achieve overall cost reduction.
[0110] 2. Simplify the construction process
[0111] Ultralight aggregate concrete high-efficiency self-insulating materials usually have an integrated design, which can reduce process and labor costs during construction. For example, ultralight aggregate concrete high-efficiency self-insulating blocks can be directly laid without the need for additional insulation layers, which improves construction efficiency and shortens construction periods.
[0112] 5. Promote sustainable development of the construction industry
[0113] 1. Reduce environmental impact
[0114] The use of ultra-light aggregate concrete high-efficiency self-insulating materials can reduce greenhouse gas emissions and environmental pollution in the energy production process. Reducing dependence on fossil fuels will help alleviate global climate change issues. At the same time, ultra-light aggregate concrete high-efficiency self-insulating materials use renewable resources or industrial waste as raw materials, realizing the recycling of resources and reducing the exploitation of natural resources.
[0115] 2. Comply with green building standards
[0116] As people pay more and more attention to environmental protection and sustainable development, green buildings have become the trend of future building development. Ultra-light aggregate concrete high-efficiency self-insulating materials meet the requirements of green buildings and can support buildings in obtaining green building certification. This not only enhances the value of buildings, but also promotes the entire construction industry to develop in a sustainable direction.
[0117] 6. Improving the seismic performance of buildings
[0118] 1. Reduced weight
[0119] The density of ultra-light aggregate concrete high-efficiency self-insulating materials is much lower than that of ordinary concrete and autoclaved concrete. The use of ultra-light aggregate concrete can significantly reduce the weight of a building. Under the action of an earthquake, the weight of a building is an important factor affecting the magnitude of the earthquake force. The reduction in weight reduces the inertial force generated by the earthquake, thereby reducing the earthquake load borne by the structure and reducing the degree of damage to the building caused by the earthquake.
[0120] 2. Good deformation performance
[0121] The elastic modulus of the density of ultra-light aggregate concrete high-efficiency self-insulating materials is low, and its deformation capacity is stronger than that of ordinary concrete of the same grade. When an earthquake occurs, it can better absorb and dissipate earthquake energy, buffer the impact of seismic waves through its own deformation, reduce the stress and deformation of the structure, and reduce the risk of structural damage.
[0122] 3. Damping characteristics
[0123] Ultra-light aggregate concrete high-efficiency self-insulating materials have a high damping ratio. Damping is the ability of a structure to dissipate energy during vibration. A high damping ratio means that under the action of an earthquake, the structure can more quickly convert seismic energy into other forms of energy such as heat, thereby reducing the vibration amplitude and duration of the structure and enhancing the seismic performance of the building.
[0124] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. An ultra-light aggregate concrete high-efficiency self-insulating material, characterized by: The invention comprises the following components in parts by weight: 12-60 parts of silicate cement, 4-30 parts of mineral powder, 0.2-1.1 parts of aerogel, 0.2-2.1 parts of glass microspheres, 2-30 parts of fly ash, 1-3 parts of polystyrene particles, 0.2-2.5 parts of activator, 1-6 parts of foaming agent, 0.2-0.5 parts of foam stabilizer, 0.05-0.35 parts of water reducer, 0.5-1.2 parts of reinforcing agent and 10-40 parts of water.
2. A building material according to claim 1, characterized in that: The silicate cement is silicate cement with a grade of 42.5 or above.
3. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The mineral powder is granulated blast furnace slag powder.
4. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The aerogel is inorganic oxide aerogel powder or organic aerogel powder composed of nanometer-scale particles.
5. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The glass microspheres are hollow glass microspheres.
6. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The activator is a base activator.
7. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The foaming agent is a composite foaming agent.
8. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The foam stabilizer is triethanolamine or silicone polyether emulsion or silicone polyether emulsion.
9. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The water reducing agent is a melamine-based high-efficiency water reducing agent or a polycarboxylic acid-based high-performance water reducing agent.
10. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The reinforcing agent is a nucleating substance.
11. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 10, characterized in that: The reinforcing agent is nano calcium carbonate.
12. The ultra-light aggregate concrete high-efficiency self-insulating material according to claim 1, characterized in that: The water is pollution-free natural water.
13. A building material according to claim 1, characterized in that: The fly ash is fine solid particles in the flue gas ash produced by coal combustion.
14. A method for preparing the ultra-light aggregate concrete high-efficiency self-insulating material as claimed in any one of claims 1 to 11, characterized in that: The following steps are involved: S1: Mix silicate cement, mineral powder, fly ash, water reducing agent, activator, reinforcing agent and water in the above proportions and use a mixer to mix into slurry; S2: dilute the composite foaming agent with water at a ratio of 1:10, add a foam stabilizer to make the foaming agent foam, and then fully blend it with the slurry; S3: Add polystyrene particles, aerogel and glass beads into the slurry and continue stirring.
Citation Information
Patent Citations
A High-Stability Ultralight Pumpable Foamed Concrete and Its Preparation Method
CN113800864B